4-[Tris(1H-pyrazol-1-yl)methyl]phenol - Chen, Xiao-Yan (International Union of Crystallography, 2011)
The title compound, C(16)H(14)N(6)O, was prepared by the condensation of 4-(trifluoromethyl)phenol and sodium pyrazol-1-ide in a yield of 58%. The dihedral angles formed by the planes of the pyrazole rings are 50.7 (2), 71.2 (3) and 95.8 (2)°. The molecules are associated into dimers by pairs of intermolecular O—H⋯N hydrogen bonds involving the hydroxy groups and pyrazole N atoms. In addition, π–π stacking between the phenol rings of these inversion-related dimers is observed, with a ring centroid-to-centroid distance of 3.9247 (10) Å.